Novel integrin-dependent platelet malfunction in siblings with leukocyte adhesion deficiency-III (LAD-III) caused by a point mutation in FERMT3 - Jurk, Kerstin; Schulz, Ansgar S.; Kehrel, Beate E.; Räpple, Daniel; Schulze, Harald; Möbest, Dieter; Friedrich, Wilhelm W.; Omran, Heymut; Deak, Erika; Henschler, Reinhard; Scheele, Jürgen S.; Zieger, Barbara (Thrombosis and Haemostasis, 2010)
Leukocyte adhesion deficiency-III (LAD-III) also called leukocyte adhesion deficiency-1/variant (LAD1v) is a rare congenital disease caused by defective integrin activation of leukocytes and platelets. Patients with LAD-III present with non-purulent infections and increased bleeding symptoms. We report on a novel integrin-dependent platelet dys-function in two brothers with LAD-III syndrome caused by a homozygous mutation 1717C>T in the FERMT3 gene leading to a premature stop codon R573X in the focal adhesion protein kindlin-3. Stimulation of patients´ platelets with all used agonists resulted in a severely decreased binding of soluble fibrinogen indicating a defect in inside-out activation of the integrin αIIbβ3 (GPIIb/IIIa). Patients´ platelets did not respond to the α2β1-integrin agonist aggretin-A at all. Our data on granula secretion indicate for the first time that the thrombin receptor PAR-4 but not PAR-1 may be important in integrin-triggered granule secretion in response to thrombin. In contrast, collagen mediated platelet granule secretion was not affected in LAD-III-patients. Thus, integrin-signalling may be not essential in collagen-induced granule secretion. The patients’ peripheral blood mononuclear cells showed a severe loss of adhesion capacity to VCAM-1 and to endothelial cells compared to cells from healthy donors. Rap-1 activation after PMA stimulation could be observed in controls´ but not in patients´ cells. After haematogenesis stem cell transplantation (HSCT) the brothers showed no symptoms of bleeding or immunodeficiency and the integrin-dependent platelet and leukocyte functions normalised.
Keywords: Leukocyte adhesion deficiency; platelets; integrin; kindlin-3